Anti-aging effect of methylurolithin A and its amide derivatives on nematode Caenorhabditis elegans. (24th March 2023) - Tang, Long; Chen, Xi; Kong, Xiang-ming; Liu, Tian-wen; Feng, Xiao-qing; Chen, Fen-er; Zhuang, Zi-heng
Graphical abstract: In this study, mUA and its 9 amide derivatives were synthesized, and Caenorhabditis elegans were used to explore their anti-aging effects. Compound 6 has the most obvious anti-aging effect and good biosafety, so it is considered the most potential to be used as an anti-aging drug for further research and development. Abstract: At present, the global irreversible rapid population aging will cause serious social healthcare burden and economic downward pressure for many countries or regions. Urolithin A (UA) has received extensive attention and research due to its role in inducing mitophagy and improving muscle capacity. Methylurolithin A (mUA) and its nine amide derivatives were synthesized in this study in order to find potential drugs with better anti-aging effects. The anti-aging and biosafety of the synthesized compounds were evaluated using Caenorhabditis elegans ( C. elegans ). The results showed that among mUA and its nine amide derivatives, Cpd. 6 had the best anti-aging effect, and had good biosafety in the growth, reproduction and motility of C. elegans . Therefore, we believe that Cpd. 6 is most suitable to be considered as a potential anti-aging drug for further development and investigation.